FUNDAMENTAL PRINCIPLES OF CONSTRUCTING A FOREIGN LANGUAGE TEXTBOOK FOR SPECIFIC PURPOSES - Grigoryan, Lusine; Gevorgyan, Ruzanna (Foreign Languages for Special Purposes, 2025)
Foreign language textbooks designed for specific purposes (ESP) play a crucial role in developing specialized communication skills essential for success in professional or academic fields. Unlike general language learning resources, these textbooks are tailored to meet the distinct linguistic, cultural, and contextual needs of their target audience. They aim to equip learners with practical tools for navigating real-world situations in specific domains, such as business, medicine, law, or engineering. By focusing on relevant vocabulary, terminology, and communicative strategies, ESP textbooks enable learners to achieve high proficiency levels in their specialized areas, enhancing their overall effectiveness and competence in the field.Creating an effective ESP textbook requires adherence to several fundamental principles. These principles guide every stage of the textbook development process, ensuring that the content is relevant, practical, and adaptable to the learners’ specific goals. From conducting a comprehensive needs analysis to integrating authentic materials and task-based learning approaches, the construction of such textbooks is a carefully planned and deliberate process. Furthermore, ESP textbooks must strike a balance between teaching language skills and addressing field-specific demands, such as technical terminology, professional etiquette, and cultural awareness.The design process also emphasizes modularity, allowing educators to adapt materials for different learner levels and contexts. Flexibility is key, as the diverse needs of target audiences necessitate customizable structures and activities. Additionally, the integration of measurable learning outcomes and regular assessments ensures learners can track their progress and apply their skills confidently in professional scenarios.By following these principles, educators and textbook developers can create resources that not only teach language but also empower learners to engage effectively in their chosen fields. This article explores these foundational principles in detail, highlighting their significance and providing a blueprint for constructing foreign language textbooks tailored to specific purposes.The purpose of the article is to specify the theoretical (conceptual) foundations of designing an English language textbook that meets the modern requirements of teaching English for Specific Purposes (ESP), thus considering the conceptual foundations of designing a textbook as a systemic description of the textbook, the principles of its construction, external and internal factors influencing its content, as well as the requirements for its use.The purpose of this article is to outline the theoretical foundations for designing an English language textbook that aligns with modern requirements for teaching English for Specific Purposes (ESP). This includes examining the conceptual framework for textbook development as a systematic description encompassing the textbook's structure, guiding principles, external and internal factors influencing its content, and the practical requirements for its effective use in educational settings.
Keywords: assessment criteria; authentic materials; content selection; cultural context; curriculum design; foreign language; interdisciplinary approach; language proficiency; language skills; learning outcomes; needs analysis; specific purposes (SP); target audience; task-based learning; textbook construction